Do Crude Oil Prices Affect Energy Consumption in Nigeria? - , Eugene Iheanacho (Archives of Current Research International, 2018)
This study examines the dynamic effects of crude oil price on energy consumption in Nigeria over the period 1975-2013 using the autoregressive distributed lag (ARDL) bounds testing approach to cointegration. The results show that crude oil price is a significant long-run and short-run determinant of energy consumption in the Nigerian economy. A positive and significant relationship is found between crude oil price and energy consumption in the economy with and without the incorporation of the presence of a structural break point in the series. The results in general highlight the need to lessen the dependence of economic activities that generate energy demand on crude oil price through the development of sustainable renewable energy system in the Nigerian economy.